AB0817 Improving care for patients with osteoarthritis in five european countries: the jigsaw-e patient panel. (15th June 2017) - Blackburn, S; Meesters, J; Wit, M De; Campbell, L; Rhodes, C; Schiphof, D; Vlieland, T Vliet; Bierma-Zeinstra, S; Østerås, N; Pais, S; Roos, E; Evans, N; et al.
Abstract : Background: EULAR guidelines for osteoarthritis (OA) endorse high quality care and support to self-manage with core recommended treatments such as exercise, weight loss and the provision of written information and education. An EU-funded project, Joint Implementation of Guidelines for oSteoArthritis in Western Europe (JIGSAW-E) 1, aims to improve the management of OA across five European countries (UK, Netherlands, Norway, Denmark, Portugal) by implementing an intervention to enhance the OA consultation. Coordinated, cross-border Patient and Public Involvement and Engagement (PPIE), working in active partnership with the project team, is an essential component of JIGSAW-E. Objectives: To describe the PPIE in the JIGSAW-E project. Methods: A two-day international workshop established the JIGSAW-E Patient Panel to act as the voice of patients and the public in the project and to co-develop clear information and resources for patients. Panel members meet regularly with the project teams in each country. The Patient Panel is coordinated and supported by dedicated PPIE teams in the UK and Netherlands. Results: The JIGSAW-E Patient Panel consists of Patient Champions and patient representatives from newly established or existing patient groups in each of the five countries. The Patient Champions form a core group of seven patient representatives who work closely with the Patient Panel and the JIGSAW-E team. PPIE activities have included: One Patient Champion sits on the JIGSAW-E project steering committee. In the Netherlands, Patient Panel members substantially contributed to the translation and cultural adaptation of a guidebook for patients with OA. This process will continue as JIGSAW-E is rolled out in each of the five countries. Patient Panel members in the UK have helped refine an OA Quality Indicator questionnaire 2 for use in JIGSAW-E. A glossary of terms has been developed to support the involvement of Patient Panel members throughout the project. Conclusions: Effective and meaningful PPIE is a central component to delivery and success of raising awareness and implementing the OA management recommendations on a national level. The Patient Panel represents a step forward in international collaboration of PPIE within implementation projects. The Patient Panel is producing culturally appropriate and relevant information and resources for patients in five European countries. Future activities may include the development of patient stories to support increased adoption of JIGSAW-E, providing the patient perspective during training of health care professionals, and the digitisation of patient resources into Smartphone or tablet Apps. References: https://goo.gl/a4xYUV. Blackburn et al. Res. Involvement and Engagement (2016) 2:5. doi: 10.1186/s40900-016-0019-x. Acknowledgements: JIGSAW-E is funded via the West Midlands AHSN by EITHealth. Funding from the WM AHSN, the Regional Innovation Fund NHS England and Shropshire CCG. KD is part funded by a Knowledge Mobilisation Research Fellowship (KMRF201403002) from the NIHR. Disclosure of Interest: None declared